HPLC Determination of Phenolic Acids in Infected Plants of Chickpea - Sharma, A.; Joshi, N.; Sharma, P.; Sharma, S.; Maheshwari, A. (Asian Journal of Chemistry, 2011)
Phenolic acids are active antimicrobial compounds and root signaling molecules that play important roles in plant defense responses. The effect of Macrophomina phaseolina infection was evaluated in chickpea at different progression periods of infection, in relation to the variation in phenolic compounds within the host. Both in vivo and in vitro studies were carried out for finding changes in the level of polyphenols in two different aged plants of four cultivars of chickpea. Overall, an increment in the amount of total phenolics within a methanolic extract of diseased leaf tissues as compared to the healthy tissues was observed following infection. Further thin-layer chromatography (TLC) and high performance liquid chromatography (HPLC) analyses were used to identify the host's phenolic compounds, which were mostly affected by the host-pathogen interaction. The number of peaks identified were more in infected plants than in control ones. A range of phenolic acids were detected among which 10 were identified by HPLC viz., cinnamic acid, p-coumaric acid, o-coumaric acid, sinapic acid, ferulic acid, gallic acid, chlorogenic acid, kaempferol, myricetin and caffeic acid. The degree of accumulation of these phenolics in infected plants was found to be more than that of untreated plants.